Three new species of Cancellariidae (Gastropoda: Neogastropoda) from northeast Brazil with first record of Gergovia for the Atlantic ocean - de Barros, José C. N.; de Lima, Silvio F. B. (Zootaxa, 2007)
Brocchinia verheckeni n. sp. and Brocchinia harasewychi n. sp. are described from several stations from 340 to 720m on the Continental Slope off Northeast Brazil. Brocchinia verheckeni occurred from the states of Ceará to Sergipe, and B. harasewychi was collected from the states of Pernambuco to Alagoas. Both species are considered endemic to these regions. This is the second record of the genus Brocchinia Jousseaume, 1887 in deep waters off Brazil. Brocchinia harasewychi has a protoconch with 1 ¼ whorls, which is more inflated in comparison to B. verheckeni, the body whorl has 3 spiral cords, the uppermost bordering the suture and the other 2 near mid-whorl. The body whorl of Brocchinia verheckeni has 3 strongly nodulose spiral cords and an outer lip with 5 to 6 internal denticles, while that of B. harasewychi has a smooth outer lip. The genus Gergovia Cossmann, 1899 is recorded for the first time in the Atlantic Ocean with the description of Gergovia petiti n. sp., known only from the oceanic region from Northeast Brazil, occurring from the state of Ceará to the state of Bahia, as well as in the Fernando de Noronha archipelago, probably living in the muddy substrate at depths of between 206 and 720 meters.